STUDENTS’ ABILITY IN WRITING AN INTRODUCTORY PARAGRAPH OF ARGUMENTATIVE ESSAY - RINI ANITA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
Writing well is not just an option for young people – it is necessary. They need writing skill as one of predicator of academic success and a basic requirement for participation in civic life. Seeing writing skill as one of important skill to be a well comprehended by young people, include students, writing appears as nightmare for struggling writers. Likewise, they often waste most of their time just for starting to write. This paper is intended to find out the students’ ability in writing paragraph of argumentative essay particularly in writing the introductory paragraph, general statements and thesis statement.Key Words: Ability, Introductory Paragraph, Argumentative Essay